2016
DOI: 10.11648/j.ajbls.20160403.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Administration of Aqueous Extract of <i>Ocimum gratissimum</i> (Scent Leaf) on Blood Glucose and Lipid Profile in Alloxan Induced Diabetic Albino Rats

Abstract: This study was aimed at comparing the antidiabetic and antihyperlipidemic activities of various doses (1.0, 2.0ml and 3.0ml) of aqueous extract of Ocimum gratissimum and glibenclamide (a reference hypoglycemic drug). Ninety (90) male wistar albino rats were used. The rats were divided into six groups (A, B, C, D, E and F) of five rats each. The experiment was replicated three times. The first group, A was non diabetic while B to F was made diabetic using alloxan. Results obtained showed that there was a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…ex Tedlie (Cecropiaceae family). In vivo studies demonstrated that Oc leaf extracts possess both in vitro and in vivo hypoglycemic properties [12][13][14][15][16][17][18][19]. Recently, Musanga cecropioides (Mu) leaves or stem bark extracts have shown an antidiabetic potential [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…ex Tedlie (Cecropiaceae family). In vivo studies demonstrated that Oc leaf extracts possess both in vitro and in vivo hypoglycemic properties [12][13][14][15][16][17][18][19]. Recently, Musanga cecropioides (Mu) leaves or stem bark extracts have shown an antidiabetic potential [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%